Responsibility Accounting in Supporting Good Corporate Governance Implementation: A Literature Review - Lande, Wise; Tangalayuk, Serilia; Octaviani, Fiona; Usman, Asri; Mediaty, Mediaty (Jurnal Locus Penelitian dan Pengabdian, 2026)
The dynamics of the business environment and stakeholder demands increase the urgency of implementing Good Corporate Governance (GCG), which requires a supporting system to ensure accountability and transparency. Responsibility Accounting has been identified as a potential managerial accounting mechanism for strengthening GCG principles. This study aims to examine the role of Responsibility Accounting in supporting the implementation of Good Corporate Governance. Using a literature review method with a qualitative-descriptive approach, this research analyzes national and international academic sources published between 2016 and 2025 that discuss the relationship between Responsibility Accounting and GCG. The findings indicate that this system significantly contributes to strengthening GCG principles, particularly accountability, transparency, and fairness. Responsibility Accounting enables clear tracking of responsibility, fair performance measurement based on controllable elements, and enhances the effectiveness of internal control. However, its implementation still faces challenges such as limited technological infrastructure, managerial resistance, and insufficient organizational policy support. Therefore, the successful implementation of this system requires strong top management commitment, integration with information systems, and adequate human resource capacity.